Góngora y Tirso de Molina: lo culto y lo sorprendente - Dolfi, Laura (Moderna/Comparata, 2021)
For the first time, this book parallels the works of Góngora and Tirso, analyzing their different involvement in the expressive modalities of the Baroque that both interpret and value in a hyperbolic way. With efficiency and originality, the renowned hispanist Laura Dolfi studies the style of Soledades, Panegírico, and Cigarrales, and the artifices of fiction that, in Las firmezas de Isabela and La fingida Arcadia, guide the desenlace, underlining the position of its author with respect to the literary precepts of the time (rejection or acceptance of new art and culteranismo). In addition, Góngora's role as a playwright is valued, and his plays are studied from less accustomed points of view: the dramatic characteristics, the importance of the rhythm that his verses scanned, the diffusion and the possible corruption of the text.